Die Verpleegproses - R.H. van den Berg (AOSIS, 1978)
The nursing process, which is always dynamic, relates essentially to the needs of the situation to which it must be applied, and for its meaningful implementation it calls for the nurse's intellectual, interpersonal and technological abilities. It is fundamental to the nursing philosophy which the nurse develops for herself.